2020
DOI: 10.3390/molecules25235594
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of the Cytotoxicity of Ayahuasca Beverages

Abstract: Ayahuasca is a beverage consumed at shamanic ceremonies and currently has gained popularity on recreational scenarios. It contains beta-carboline alkaloids and N,N-dimethyltryptamine, which possesses hallucinogenic effects. Only a few studies have elicited the psychoactive effects and the dose of such compounds on neurological dopaminergic cells or animals. In this work, we aimed to study the cytotoxic effects of these compounds present in ayahuasca beverages and on five different teas (Banisteriopsis caapi, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 31 publications
0
24
1
Order By: Relevance
“…A plant containing these substances-Peganum harmala (P. harmala), is used in some cases as a substitute for B. caapi, [29]. Some other plants containing DMT such as Psychotria viridis or Mimosa tenuiflora (M. tenuiflora) are added to the decoction to increase its psychoactive properties [18,28,30]. Depending on the origin and development of the plants used in the preparation of ayahuasca beverages, the chemical composition may vary, both qualitatively and quantitatively [10].…”
Section: Plants Used To Prepare Ayahuasca Decoctionmentioning
confidence: 99%
See 2 more Smart Citations
“…A plant containing these substances-Peganum harmala (P. harmala), is used in some cases as a substitute for B. caapi, [29]. Some other plants containing DMT such as Psychotria viridis or Mimosa tenuiflora (M. tenuiflora) are added to the decoction to increase its psychoactive properties [18,28,30]. Depending on the origin and development of the plants used in the preparation of ayahuasca beverages, the chemical composition may vary, both qualitatively and quantitatively [10].…”
Section: Plants Used To Prepare Ayahuasca Decoctionmentioning
confidence: 99%
“…When the aldehyde is acetaldehyde or pyruvic acid, simple carboline alkaloids are formed and are referred to as "beta-carbolines" (in the case of acetaldehyde) or as "harmala alkaloids" (harmine, harmaline), as they were originally isolated from the plant Peganum harmala. They are also found, for example, in the plants of Passiflora incarnata L. These substances are able to reversibly block the activity of MAO enzyme subtype A [18,29]. MAO naturally degrades endogenous neurotransmitters and potentially dangerous exogenous amines that could be accidentally consumed in the diet.…”
Section: Structure and Physico-chemical Properties Of Ayahuasca Compo...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are several studies that report therapeutic properties. Recently their proprieties were reported as antimicrobial and antioxidant agents [ 52 ], as well as their effect over dopaminergic neuron cells [ 53 ]. Studies have shown that a single dose of Ayahuasca leads to a rapid reduction in depressive symptoms, and this reduction is maintained for three weeks [ 54 , 55 ].…”
Section: Ayahuasca (“Hoasca”)mentioning
confidence: 99%
“…This paper [ 1 ] reports important data on the cytotoxicity of Ayahuasca beverages on dopaminergic cells. However, some of the reported information could be misinterpreted; as such, we would like to clarify a few issues in order to avoid misleading the reader.…”
mentioning
confidence: 99%